(untitled) (GIST – Education and Learning Research Journal, 2019)
Using a reflective exercise designed for this study, Guatemalan educators explored their students’ and their own cultural capital. The cultural capsule exercise served as a vehicle to bring delicate issues that are difficult to discuss, but that are essential to effective schooling, to reflective conversations. A total of 108 teachers went beyond identifying problems and detailing frustrations, to exploring possibilities for action. Participants converged in sharing perspectives that Guatemala is a culture of silence, and used examples to illustrate how this perpetuates the limitations of the country’s schoolhouse. Findings reveal the teachers were challenged to focus on what can be accomplished. Qualitative data analyzes, conducted using symbolic convergence theory to establish recurrent and idea generation, suggest a need for further examination of how the sociocultural educational mandates delimit teachers’ ability to adjust the curriculum in consideration of learners’ funds of knowledge. Keywords: teachers’ voices, cultural capital, funds of knowledge, reflective educators, diverse indigenous cultures of Guatemala Resumen Docentes de una comunidad de Guatemala examinaron el capital cultural de sus estudiantes y de si mismos, usando un ejercicio desarrollado para este estudio. El ejercicio de la cápsula cultural sirvió de vehículo para aportar a la conversación temas que, aunque delicados y difíciles de aproximar, son esenciales para establecer sistemas escolares efectivos. Un total de 108 maestros compartieron y detallaron sus frustraciones, y comenzaron a explorar cambios que ellos mismos podrían llevar a cabo. Los participantes convergieron en sus ideas para verificar sus puntos de vista que Guatemala es una cultura de silencio. Ellos ofrecieron ejemplos que detallaron el por qué, este silencio perpetúa y limita la escolarización. Datos cualitativos, documentados usando la teoría de la convergencia simbólica, se usaron para establecer temas que se repitieron y generaron ideas. Investigaciones futuras han de examinar el contexto educacional y sociocultural que evidentemente delimita cómo en Guatemala los maestros y sus estudiantes se desenvuelven en las escuelas, y consideran sus fondos de conocimientos. Palabras Claves: voces de los maestros, el capital cultural, educación liberatoria, culturas indígenas de Guatemala